2012
DOI: 10.1254/jphs.11240fp
|View full text |Cite
|
Sign up to set email alerts
|

Synergism Between Interleukin (IL)-17 and Toll-like Receptor 2 and 4 Signals to Induce IL-8 Expression in Cystic Fibrosis Airway Epithelial Cells

Abstract: Cystic fibrosis (CF) is the most common lethal inherited disorder and is caused by mutations in the gene encoding the CF transmembrane regulator (CFTR). The CF lung expresses a profound proinflammatory phenotype that appears to be related to a constitutive hypersecretion of interleukin (IL)-8 from airway epithelial cells in response to microbial infection. Since overproduction of IL-8 in CF contributes to massive bronchial infiltrates of neutrophils, identification of the pathways underlying IL-8 induction cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In the literature, it has been reported that TNF- α , IL-1 β , IL-22, Oncostatin M, IFN γ , BAFF, and CD40L can all synergize with IL-17A to upregulate IL-17A target genes or their respective target genes [129, 139, 145–147]. In addition, IL-17A also synergizes with TLR2 and TLR4 ligands to increase IL-8 production in a human cystic fibrosis bronchial epithelial cell lines [148]. In an in vivo context, this may be where IL-17A induces its most potent effects, within the cytokine milieu of an inflammatory setting to further potentiate the inflammatory response.…”
Section: Il-17a-induced Gene Expression In the Airwaymentioning
confidence: 99%
“…In the literature, it has been reported that TNF- α , IL-1 β , IL-22, Oncostatin M, IFN γ , BAFF, and CD40L can all synergize with IL-17A to upregulate IL-17A target genes or their respective target genes [129, 139, 145–147]. In addition, IL-17A also synergizes with TLR2 and TLR4 ligands to increase IL-8 production in a human cystic fibrosis bronchial epithelial cell lines [148]. In an in vivo context, this may be where IL-17A induces its most potent effects, within the cytokine milieu of an inflammatory setting to further potentiate the inflammatory response.…”
Section: Il-17a-induced Gene Expression In the Airwaymentioning
confidence: 99%
“…Cell culture. 16HBE14o-cells were generated as reported previously 34 and grown in fibronectin/vitrogen/ BSA-coated flask in MEM (Invitrogen, Inc., Carlsbad, CA, USA) 35 . These cells were maintained in MEM supplemented with 10% fetal bovine serum, 2% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Specific cell source, modulation of culture conditions and/or specific stimuli might explain these discrepancies. A strong synergism between TLR2/PGN- and TLR4/LPS-mediated IL-8 production and IL17A was found in human bronchial epithelial cell lines [126]. Recently, genotyping of TLR polymorphisms revealed that CF airway epithelial cells are homozygous for TLR1 SNP 1602S and possess a diminished innate immune response towards Mycobacterium abscessus infection .…”
Section: Innate Immune Activation In Cf Lung Diseasementioning
confidence: 99%